Beta blockers and long-term outcome after coronary artery bypass grafting: a nationwide observational study. Issue 5 (31st January 2022) - Lindgren, Martin; Nielsen, Susanne J; Björklund, Erik; Pivodic, Aldina; Perrotta, Sossio; Hansson, Emma C; Jeppsson, Anders; Martinsson, Andreas
Abstract: Aims: Beta blockers are associated with improved outcomes for selected patients with cardiovascular disease. We assessed long-term utilization of beta blockers after coronary artery bypass grafting (CABG) and its association with outcome. Methods and results: All 35 184 patients in Sweden who underwent first-time isolated CABG between 1 January 2006 and 31 December 2017 and were followed for at least 6 months were included in a nationwide observational study. Multivariable Cox regression models using time-updated data on dispensed prescriptions were used to assess associations between different types of beta blockers and outcomes. The primary outcome was major adverse cardiovascular events (MACEs), a composite of all-cause mortality, stroke, and myocardial infarction (MI). Subgroup analyses were performed in patients with and without previous MI, heart failure, and reduced left ventricular ejection fraction (LVEF). Median follow-up was 5.2 years (range 0–11). At baseline, 33 159 (94.2%) patients were dispensed beta blockers, 30 563 (92.2%) of which were cardioselective beta blockers. After 10 years, the dispensing of cardioselective beta blockers had declined to 73.7% of all patients. Ongoing treatment with cardioselective beta blockers was associated with a slight reduction in MACEs [hazard ratio (HR) 0.93, 95% confidence interval (CI) 0.89–0.98, P = 0.0063]. The reduction was largely driven by a reduced risk of MI (HR 0.83, 95% CI 0.75–0.92, P = 0.0003), while there was no significant reduction in all-cause mortality (HR 0.99, 95% CI 0.93–1.05) and stroke (HR 0.96, 95% CI 0.87–1.05). The reduced risk for MI was consistent in all the investigated subgroups. Conclusion: Ongoing treatment with cardioselective beta blockers after CABG is associated with a reduction in MACEs, mainly because of reduced long-term risk for MI. The association between cardioselective beta blockers and MI was consistent in patients with and patients without previous MI, heart failure, atrial fibrillation, or reduced LVEF.